الإجراءات الإدارية المتعلقة بوباء كوفيد-19 من منظور القواعد الفقهية: دراسة مقارنة بالقانون الصحي الليبي: (Administrative Measures Related to the Covid-19 Pandemic in the Light of Legal Maxims (al-Qawa’id al-Fiqhiyyah): A Comparative Study with Libyan Health Act) - لؤي عبدالسلام محمد أبوسعد; روزمان بن محمد نور; محمد حافظ بن جمال الدين (At-Tajdid - Intellectual Refereed Journal, 2022)
This study aims to evaluate the legislative treatment of the (Covid 19) epidemic in terms of measures taken to confront it in the Libyan Health Law 106/1973 and its implementing regulation in comparition with al-Qawa’id al-Fiqhiyyah to to highlight its legislative values and to cite some legal studies in the recent judicial applications. The research followed the descriptive analytical approach; view these actions and the rooting of its provisions through the rules of Islamic jurisprudence, and it has been shown that the treatment of these rules of Islamic jurisprudence is characterized by comprehensiveness. The fiqh approach also shown that the treatment establishes the legitimacy of these procedures, determines the controls for their application, and addresses the effects resulting from them, in a way that is no less sophisticated than what has been reached by the latest legislation, and is also characterized by objectivity and stability. It stems in its dealing with the relevant legal concepts - such as the concepts of right and freedom - from the constants of Shari’a and its overall purposes (maqāṣid) that those rules reflect. The research recommended that there is a necessity of deeper applied studies of these rules in different legal branches, and the need to benefit from them in the areas of legislation, administration and elimination at the theoretical and practical levels, to make them a criterion for reviewing legislation, and then implementing it optimally; This is due to its prominent importance in clarifying the provisions of calamities and developments, as well as the research recommended to include the subject of jurisprudence in the teaching curricula of law faculties and institutes of justice and administration. Keywords: Pandemic, developments, administrative procedures, jurisprudential rules.